2016
DOI: 10.1111/add.13602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a national naloxone programme on ambulance attendance at overdose incidents: a controlled time–series analysis

Abstract: Background and AimsIt has been suggested that distributing naloxone to people who inject drugs (PWID) will lead to fewer attendances by emergency medical services at opioid‐related overdose incidents if peer administration of naloxone was perceived to have resuscitated the overdose victim successfully. This study evaluated the impact of a national naloxone programme (NNP) on ambulance attendance at opioid‐related overdose incidents throughout Scotland. Specifically, we aimed to answer the following research qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Ambulance call‐outs for overdoses within a pre‐determined time‐frame post‐THN receipt are suggestive of increased opioid use. However, ambulance calls are an important and expected aspect of THN distribution, administration and after‐care.…”
Section: Measuring Unintended Consequences Of Thnmentioning
confidence: 99%
“…Ambulance call‐outs for overdoses within a pre‐determined time‐frame post‐THN receipt are suggestive of increased opioid use. However, ambulance calls are an important and expected aspect of THN distribution, administration and after‐care.…”
Section: Measuring Unintended Consequences Of Thnmentioning
confidence: 99%
“…Research has additionally indicated that peers trained in overdose response may continue to use non-evidence-based strategies alongside recommended strategies [18,21,36] and that they may be deterred from using naloxone because it can prompt withdrawal symptoms which make victims aggressive ('over-antagonism') [37]. Furthermore, studies have suggested that THN might reduce ambulance call-outs resulting in fatalities from the recurrence of respiratory depression if lay responders leave victims unattended [18,[38][39][40], although this has also been refuted [15,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will need to look at the extent to which widespread THN provision, as perhaps achieved in Scotland McAuley et al, 2017), Norway (MadahAmiri et al, 2017) and several states in the US (Walley et al, 2013), results in reduction in opioid overdose mortaliy at state or national level, and what naloxone coverage rates are required to achieve this effect.…”
Section: Naloxone Coveragementioning
confidence: 99%